Genotyping, antimicrobial resistance and virulence factor gene profiles of vancomycin resistance Enterococcus faecalis isolated from blood culture. (August 2017) - Armin, Shahnaz; Fallah, Fatemeh; Karimi, Abdollah; Rashidan, Marjan; Shirdust, Mehdi; Azimi, Leila
Abstract: Background: Enterococcus spp. is the common of intestinal micro flora in humans but nowadays this gram-positive bacterium causes the variety of nosocomial infections. Resistance to antibiotic and also, presence of different virulence genes in the enterococcus spp. can change it to problematic microorganisms in the health care centers. The aim of this study was determined the genotyping, antimicrobial resistance and virulence factor gene profiles of vancomycin resistance Enterococcus faecalis isolated from blood culture. Methods: In this study, enterococcus isolated from BACTEC was collected and antibiotic susceptibility testing was done according to CLSI recommendation. Important virulence genes and vancomyci resistance genes were detected by PCR and molecular typing was performed by RAPD PCR assay. Results: Nine enterococcus collected from 194 positive BACTEC and seven out of nine were vancomycin-resistant enterococcus (VRE). vanA gene observed in all VRE and none of strains carried vanB and vanC genes. efbaA and gelE virulence factors have been detected in all strains. ace, esp, and cyl virulence factors genes harbored in two, seven and eight isolates respectively. asaI was not detected in any strains. All seven VRE isolates were related to the one specific molecular type and two different molecular types observed in the two vancomycin susceptible enterococci according to molecular epidemiology results. Conclusion: More prevalence of the VRE in enterococcus isolated from BACTEC is so important and on the other hand high genetic relationship in the isolated VRE can be very considerable for nosocomial infection committee in the hospital. Highlights: This study indicated that antibiotic resistant in VRE strains. This study indicated that the importance of virulence factor in VRE. The results of this study can be very useful for nosocomial infection control committee. The results of this study showed the importance of antibiotic prescription, especially in hospitalized patients.